POTENSI DAYA TARIK WISATA AIR TERJUN NUNGNUNG SEBAGAI DAYA TARIK WISATA ALAM - I Gusti Ngurah Fredi Firawan; Ida Bagus Suryawan (JURNAL DESTINASI PARIWISATA, 2016)
Nungnung Waterfal is located in Pelaga Village, Petang District, Badung Regency. Nungnung Waterfal have several potentials that can be developed into a natural taourist attraction. It is the researchers wanted to know the potential of what is owned by NungnungWaterfall that can be developed into a tourist attraction. Types of data and data sources used are the data Qualitative, Quantitatif, primary data and secondary data. Collection data by Observasi, interviews, library, and using purpose sampling method, data analytic method using qualitative descriptive that applies the facts found in the field. Nungnung Waterfallhas the potential of natural and artificial potential that could be developed into a tourist attraction. Natural potential possessed NungnungWaterfallis landscapes, mountains, waterfalls, and forests. As for the potential of artificial owned by Nungnung Waterfallnamely supporting facilities including a gazebo for resting place for tourists and take pictures in the area of Nungnung Waterfall.